Factors associated with practice on self-administration of eye drop instillation among glaucoma patients attending Eye clinic, Teaching Hospital Jaffna - Meera, S.; Ameliya Rachel, J. A.; Jegapragash, V.; Malaravan, M. (University of Jaffna, 2023)
Background: Glaucoma is a leading cause of blindness worldwide. Which requires almost life-long topical medication therapy. Unlike oral medications, while using eye drops the pharmacological action can be greatly diminished by undermedicated and overmedicated. Inadequate dispensing can also lead to bacterial infection. Adequate practice about self- administration of eye drops instillation is crucial for successful glaucoma management. Objective: To assess the practice of self-administration of eye drop instillation and the associated factors among glaucoma patients attending Eye Clinic, Teaching Hospital Jaffna. Methodology: A hospital-based observational descriptive study was carried out from September 2023 to October 2023. A systematic random sampling method was used to select 184 participants. An observational checklist was used to assess the practice of eye drop instillation. Data was analyzed by using SPSS version 27. The chi-square test was used find to the associated factors. Ethical approval was obtained from ERC, Faculty of Medicine, University of Jaffna. Results: Glaucoma patients who attended the Eye clinic, Teaching Hospital Jaffna, were approached and the respondent rate was 87.5%. The age of the participants varied from 26 years to 83 years old with a mean age of 58.93 (SD=15.398). More than half (54%, n=87) of the participants were female and the majority of them were married (76.4%, n= 123). Only a small portion of participants have educational qualifications above ordinary level (33.6% n=38). Practice on self-administration was categorized as poor practice and good practice. Two-thirds of the participants were having poor practice in self-instillation (67.7% n=109). The factors associated with the practice were the frequency of eye drops per day (p=0.038) and Knowledge (p=0.006). Conclusion: The practice of self-administration of eye drop instillation was poor among glaucoma patients who attended Eye Clinic Teaching Hospital Jaffna. The health care providers should be more attentive towards patients’ practice regarding eye drop administration. Interventions such as asking patients how they take their eye drops and observing individuals’ administration techniques are recommended.
Keywords: Glaucoma; Knowledge; Practice; Instillation; Teaching Hospital Jaffna